2014
DOI: 10.1007/s11468-014-9846-5
|View full text |Cite
|
Sign up to set email alerts
|

Single Plasmon Switching with n Quantum Dots System Coupled to One-Dimensional Waveguide

Abstract: Switching of a single plasmon interacting with n equally spaced quantum dots coupled to one-dimensional surface plasmonic waveguide is investigated theoretically via the real-space approach. We showed that the transmission and reflection of a single plasmon can be switched on or off by dynamically tuning and changing the number of the equal transition frequencies of the QDs. Increasing the number of doped QDs having the equal transition frequencies results in the wide -band reflection of a single plasmon and t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 39 publications
2
25
2
Order By: Relevance
“…3(a)) disappears when R=80nm. The above result suggests the exciton-plasmon coupling effect could be neglected when the interparticle distances longer than about 80nm for the other parameters set in this paper, which is quite different from the previous results [4][5][6][7][8][9][10], where it was found that there will be a single complete reflection peak when the frequency of the propagating plasmon is resonant with that of the bare exciton. However, our result shows that there could not be appeared a complete reflection peak even when sp    0 because of the plasmonic effect of the MNP on the SQD at the frequencies of the classic optical induced field different from 3eV.…”
Section: Theoretical Analysis and Numerical Resultscontrasting
confidence: 94%
“…3(a)) disappears when R=80nm. The above result suggests the exciton-plasmon coupling effect could be neglected when the interparticle distances longer than about 80nm for the other parameters set in this paper, which is quite different from the previous results [4][5][6][7][8][9][10], where it was found that there will be a single complete reflection peak when the frequency of the propagating plasmon is resonant with that of the bare exciton. However, our result shows that there could not be appeared a complete reflection peak even when sp    0 because of the plasmonic effect of the MNP on the SQD at the frequencies of the classic optical induced field different from 3eV.…”
Section: Theoretical Analysis and Numerical Resultscontrasting
confidence: 94%
“…Kim et al principally constructed a switch that can be used as a tristate gate. 52,53 By tuning and changing the number of equal transition frequencies of quantum dots coupled to one-dimensional SPP waveguide, the transmission and reflection of a single plasmon can be switched on or off (Figure 5a). Chang et al also developed a single photon transistor that can act as a non-linear two-photon switch for the SPPs propagating on an NW.…”
mentioning
confidence: 99%
“…3a, the transmission spectra exhibit an oscillatory pattern with half of the wavelength of the propagating plasmon as a period in terms of spacing between From Fig. 2b, c, we also found that the order of the QDs can influence on the scattering of the incident plasmon, which is quite different with the case of a two-QD system [21,22]. Especially, we can construct a half-transmitting mirror with the three-QD system by controlling the transition frequencies of QDs and setting the spacing kL 1 as 1.37π, as shown in Fig.…”
Section: Theoretical Analysis and Numerical Results Of The Transmissimentioning
confidence: 77%
“…Many theoretical [5][6][7][8][9][10][11][12][13][14][15] and experimental [16][17][18] works reported the photon scattering in different quantum systems. In the previous studies, the authors have mainly considered the scattering properties of a single photon interacting with one emitter and several emitters, and they mainly focus on the case where the quantum emitters are all equally spaced each other [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%